A web tool for the identification of potential interactive effects of chemical mixtures. - Vyskocil A; Drolet D; Viau C; Lemay F; Lapointe G; Tardif R; Truchon G; Baril M; Gagnon N; Gagnon F; Bégin D; Gérin M (Journal of Occupational & Environmental Hygiene, 2007)
This project was undertaken to develop a toxicological database allowing the identification of possible additive or other interactive effects of mixtures present in the work environment. In the first phase of the project, whose findings have already been published, critical toxicological data were compiled for each of the 695 chemical substances in the Quebec Occupational Health Regulation, allowing the prediction of potential additivity among components of a mixture. In the second phase of this project, the types of interactions for mixtures most likely to be found in workplaces and for which primary literature data are available were specified. The toxicological data were evaluated only for realistic exposure concentrations up to the short-term exposure limit or ceiling value or five times the 8-hr time-weighted average (TWA) permissible exposure limit (PEL) for human data and up to 100 times the 8-hr TWA PEL or ceiling value for animal studies. In total, 675 studies were evaluated covering 209 binary mixtures of substances. For the majority of cases where potential additivity was identified in Phase 1, there is a lack of toxicological data in the primary literature. In these cases, the results of the first phase will be useful as the default hypothesis. The resulting database integrates the results from both phases of the project. A web-based computer tool allows the user to determine whether there is potential additivity or interaction among components of a mixture.